2019
DOI: 10.1016/j.jclepro.2019.117822
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of ammonia and greenhouse gas emissions from stored cattle slurry using acidifiers and chemical amendments

Abstract: Emissions of greenhouse gas (GHG) and ammonia (NH 3 ) from cattle and cow slurry storage can be minimised by acidification. A knowledge gap exists to find chemical amendments that are suitable and cost effective to mitigate both GHG and NH 3 gases simultaneously. This study showed that ferric chloride, sulphuric acid, alum and acetic acid reduced NH 3 by 96%, 85%, 82% and 73%, respectively. In terms of methane (CH 4 ), ferric chloride, alum, sulphuric acid and acetic acid reduced emissions by 98%, 96%, 95% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 32 publications
2
37
1
2
Order By: Relevance
“…However, concerns remain about the risks associated with H 2 SO 4 handling, requiring trained staff, due to its (i) corrosiveness, (ii) possible development of volatile sulphurcontaining compounds (H 2 S) and (iii) foam formation during the addition to the slurry, limiting its wider use [12]. As alternatives for slurry acidification, other acids were studied by Regueiro et al and Kavanagh et al [34,38], but none were so efficient and cost-effective as H 2 SO 4 . Furthermore, H 2 SO 4 supplies sulphur, an important plant macronutrient [34].…”
Section: Acidificationmentioning
confidence: 99%
“…However, concerns remain about the risks associated with H 2 SO 4 handling, requiring trained staff, due to its (i) corrosiveness, (ii) possible development of volatile sulphurcontaining compounds (H 2 S) and (iii) foam formation during the addition to the slurry, limiting its wider use [12]. As alternatives for slurry acidification, other acids were studied by Regueiro et al and Kavanagh et al [34,38], but none were so efficient and cost-effective as H 2 SO 4 . Furthermore, H 2 SO 4 supplies sulphur, an important plant macronutrient [34].…”
Section: Acidificationmentioning
confidence: 99%
“…A reduction of pH of slurry has been shown to reduce ammonia gas emissions and also to inhibit bacterial processes involved in the release of greenhouse gases (GHG) (Sommer and Husted, 1995). Kavanagh et al (2019) evaluated the efficacy of common chemical byproduct amendments for acidification of stored slurry/manure for the purposes of reducing ammonia gas emissions. While lacto-gypsum was not evaluated in this previous study, the low pH may be conducive to achieve the desired reduction in slurry pH (<5.5) while not introducing contaminants such as heavy metals etc.…”
Section: Concentration Of Nutrients and Trace Elements Comparison With European Union (Eu) Regularitymentioning
confidence: 99%
“…For this reason, changes in ammonia concentrations and pH are substantial causes of ammonia gas emissions [8,9]. It has been reported that ammonia concentrations can be controlled by using oxidizing agents, such as iron chloride, sulfuric acid [35,36], or various chemical compounds [5] that reduce ammonia emission from livestock manure. Furthermore, the effects of SB and SC in manure were evaluated as they possess activities of pathogen inhibition by antimicrobial peptide production and pH reduction [21,37].…”
Section: Changes In Ph and Growth Of Hab In Manure By Yeast Treatmentmentioning
confidence: 99%